1993
DOI: 10.1080/09064709309410171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perches at Different Positions in Conventional Cages for Laying Hens of Two Different Strains

Abstract: Research Station, S-755 97 Uppsala, Sweden). Effect of perches at different positions in conventional cages for laying hens of two different strains.Production, health and behaviour were studied in 648 White Leghorn hens of two strains, LSL and Shaver 288, housed in three-tier battery cages (four hens per cage, 600 cm2 per hen) with three treatments; two with a perch fitted across the cage, 17 (PB) or 24 cm (PC) from the back of the cage, respectively, and control cages without perch (NP). Introducing a perch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
28
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 13 publications
8
28
0
Order By: Relevance
“…In the present experiment, the difference in ash percentage appears to have been too slight to induce changes in stiffness or breaking strength, since the bone dimensions may vary in a different way between cage models and counteract the effect of the composition. In the present experiment, we were expecting differences because the perching rate was high (almost 100% at night, Guesdon unpublished data) in both furnished cage models and the humerus has been reported to be stronger in cages with perches [1]. The fact that biomechanical properties of the humeri were not different between cage models could be due to an insufficient power of the statistical analyses.…”
Section: Discussionmentioning
confidence: 63%
“…In the present experiment, the difference in ash percentage appears to have been too slight to induce changes in stiffness or breaking strength, since the bone dimensions may vary in a different way between cage models and counteract the effect of the composition. In the present experiment, we were expecting differences because the perching rate was high (almost 100% at night, Guesdon unpublished data) in both furnished cage models and the humerus has been reported to be stronger in cages with perches [1]. The fact that biomechanical properties of the humeri were not different between cage models could be due to an insufficient power of the statistical analyses.…”
Section: Discussionmentioning
confidence: 63%
“…So here the larger space, supposedly combined with a greater opportunity to exercise, as well as the structural enrichment in the furnished cages did not lead to a higher tibia breaking strength of the birds. Neither Abrahamsson and Tauson (1993) nor Hughes et al (1993) found any significant increase in the tibia bones of hens housed in furnished cages as compared to those kept in conventional cages, either. Our results differ from those of Hughes and Appleby (1989), who showed that installing perches in conventional cages resulted in a higher tibia breaking strength.…”
Section: Discussionmentioning
confidence: 64%
“…The hens probably performed behaviours such as wing and leg stretching, wing flapping and sand bathing more often in the furnished cages than in the conventional cages, thus strengthening their humerus bones. The arrangement of the perches in the furnished cages could have had a positive effect on humerus breaking strength, because laying hens use their wings to get on to the perches (Abrahamsson and Tauson, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Findings in foot pad alterations range from mild hyperkeratotic alterations to inflamed ulcers of the foot, known as bumble foot (WANG et al, 1998). ABRAHAMSSON and TAUSON (1993) described hyperkeratosis as a main alteration in conventional and furnished cages. The frequent finding of hyperkeratotic alterations in cage-kept laying hens is seen to be caused by the pressure load on the foot while perching or standing on the wire floor (SIEGWART, 1991;KEUTGEN et al, 1999;WEITZENBÜRGER et al, 2005).…”
mentioning
confidence: 99%